Effects of Exposure to Screen Time on Developmental Milestones and Autism-Like Symptoms in India - Yashna David, Shikha Srivastava (Journal of Informatics Education and Research, 2025)
The study aimed to compare the developmental milestones of children currently in foundational years with excessive screen time, with limited or no screen time, and their similarity with children diagnosed with autism. It examined three areas of concern, where a direct correlation is made between over-exposure to screen time causing developmental delays in foundational years, being similar to the developmental milestones of children with autism. The sample consisted of 124 parents of preschool children aged between two and six years old in India. The Child Developmental Inventory (CDI) was used to assess developmental milestones. Findings demonstrated that there was a significant difference in the developmental milestones of typically developing children with high and low screen time and that there was no significant difference when compared with children diagnosed with autism concluding that higher screen time leads to developmental delays which are similar to the developmental milestones of children diagnosed with autism. Results also revealed that screen time significantly affected some developmental milestones in autistic children, however, the impact of screen time on academic capability was not significant in both groups. Screen time has a significant impact on the developmental milestones of autistic children, and that typically developing children have similar developmental milestones, which indicates that further investigation is required to avoid the risk of incorrect diagnostic assessment for Autism in children.